Improving Rice Farming Efficiency: Insights from Stochastic Frontier Analysis in Ponorogo District - Tirta Yoga; Arief Joko Saputro; Yohana Anggriani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Using the Stochastic Frontier Analysis (SFA) approach, this study examines the technical, allocative, and economic efficiency of rice farming practices in the BPP Jenengan area, Ponorogo Regency, East Java, a central rice-producing area in Indonesia, where rice is the staple food. This study aims to evaluate the efficiency of agricultural activities in Ponorogo Regency. Fifty rice farmers were selected through simple random sampling for this study. Data were collected through direct interviews with these farmers and then analyzed using Stochastic Frontier Analysis (SFA) with Frontier software version 4.0. Maximum Likelihood Estimation (MLE) was used to estimate the model parameters. Analysis reveals that land area and seed use significantly and positively influence rice production, contributing 99% to the output. Increasing these inputs will, therefore, enhance production. Conversely, fertilizer use demonstrates a negative impact, while pesticide and labor use show no significant effects. Technical efficiency analysis reveals that most farmers (64%) operate at a technical efficiency level between 0.66 and 0.83, with an average of 0.73, indicating potential for improvement by 0.27. Furthermore, the farmer's age is a significant factor, with those aged 52-62 exhibiting a high-efficiency level, averaging 0.76. This underscores the importance of farmer age in achieving optimal efficiency. This research on rice farming efficiency can inform the development of agricultural policies and practices in Indonesia, promoting a greater focus on productivity enhancement, production cost reduction, and sustainable resource management.